Local actions for the common good: Can the application of the ecosystem services concept generate improved societal outcomes from natural resource management?. (November 2016) - Paudyal, Kiran; Baral, Himlal; Keenan, Rodney J.
Graphical abstract: Highlights: ⿢ Landscapes can provide private, common or public goods and services that are vital for human well-being and livelihoods, but these are threatened by a mix of global and local actions. ⿢ Depending on the circumstances, ecosystem services can be supplied and managed through markets or other policy arrangements to support the provision of common or public goods. ⿢ An ecosystem services approach is a promising concept for land and water management to recognize the wider benefits that ecosystems provide for the ⿿common good⿿. Abstract: Nature provides a wide range of ecosystem services (ES) that are vital for human well-being and livelihoods. The supply of these services is being threatened by local and global pressures. Managing for the provision of ES can provide a range of benefits that, in economic terms, can be defined as, private, common or public goods. Inspired by the theme ⿿local action for the common good⿿ of 7th Ecosystem Service Partnership conference held in Costa Rica, this paper examines the key issues in policy and management for production and management of ES in a way that meet the broader common good. The ES approach is not widely understood by policymakers, the general public and the private sector. While the approach is a promising contribution to providing for common good outcomes from the management of natural resources, much needs to be done to ensure that it achieves the dual purposes of maintaining and enhancing the supply of different services and improving the livelihoods of the rural poor in developing countries. Critical areas for further attention are assessments of ecosystem services in developing countries that incorporate local and indigenous knowledge, clear links to policy and decision making, public education and engagement about the value of ecosystem services and payment mechanisms that drive local actions and contribute to local livelihoods.